Monetary condition index and its changing transmission on macro-economic variables - Iqra Aslam Memon; Hummaira Jabeen (Arab Economic and Business Journal, 2018)
It has been known with time that no single transmission mechanism is enough to understand the monetary policy stance of that country. The objective of this paper is combine two transmission channel, interest rate and exchange rate so as to construct monetary condition index (MCI) for the gulf countries, namely Bahrain, Iraq, Kuwait, Oman, Qatar, Kingdom of Saudi Arabia and United Arab Emirates, so as to forecast its impact on CPI and GDP and to suggest policymakers regarding the monetary policy of the gulf countries. For this purpose, the paper applies Principal Component Analysis and Vector Auto-Regression method to construct MCI and to analyze its impulse response on CPI and GDP. This paper concludes that MCI can be used as an indicator to predict CPI and GDP of Bahrain and Qatar in long run and as an indicator to predict the GDP of Oman in medium and long run but it cannot be used as an indicator to predict CPI and GDP of Kuwait and KSA. Furthermore, this paper also concludes that strong monetary policy is needed to strengthen their economic condition.
Keywords: 330; Monetary condition index; Monetary policy; Economic condition; CPI; GDP